Оцінювання якості шкільної освіти у Шотландії на прикладі діяльності інспекторату її величності - Джурило, Аліна (Studies in Comparative Education, 2013)
Статтю присвячено організації оцінювання якості шкільної освіти у Шотландії, її структурним та функціональним елементам. У статті детально розглянуто роботу Інспекторату її Величності в Шотландії, а також коротко схарактеризовано основні відмінності у роботі інспекторів шкіл Англії та Шотландії. Окрему увагу приділено процесу самооцінювання шкіл як ключовому елементу забезпечення якості шкільної освіти. Статья посвящена организации оценивания качества школьного образования в Шотландии, ее структурным и функциональным элементам. В статье подробно рассмотрена работа Инспектората ее Величества в Шотландии, а также кратко охарактеризованы основные отличия в работе инспекторов школ Англии и Шотландии. Отдельное внимание уделено процессу самооценки школ как ключевому элементу обеспечения качества школьного образования. The quality of education is positioned as a priority education policy of the European Union in the last decade. Significance of European cooperation in the development of high quality education is how to create a common platform for quality assurance in the Member-States and in the study and analysis of existing systems of evaluation of quality of school education to enrich the theory and practice in this area. European orientation of Ukraine determines the need for the study, synthesis, critical thinking and creative application of the achievements of European countries in this area. Scotland’s experience in view of this is particularly important for Ukraine as a whole, and in particular British Scottish secondary education is positioned highly effective. The purpose of this article is to analyze the specifics of such a tool to ensure the quality of Scottish Education as Her Majesty’s Inspectorate. Considering the problem of the quality of school education in Scotland, it should be noted the intensification of attention to this issue at all levels of Scottish society, due to socio- economic transformation. It is a fact that Scottish education decentralization in the context of intensified ideas of market economy provides greater autonomy to schools: schools are considered as one of the segments of «social benefits» as a company that is able to produce quality products without external assistance , educational institution are subjects in developing ways of education and impact on educational policy. Because schools receive more autonomy (which turns into a self- developing their curricula, selection of teaching materials, the possibility of innovation, independent distribution and use of budget funds, etc.) updated the institution responsible for compliance provided educational services established by government regulations , standards. So as we can see, in Scotland in the context of a process of ongoing improvement of the quality of educational services is a permanent improvement of the relevant authorities, while the main focus while born on enhancing the role of schools and the community – parents, community – in the process. Great attention is given to schools’ self-assessment as a key element of quality assurance. Summarizing the Scottish experience emphasize that this organization evaluating the quality of school education would be very effective on the national educational plane, which would allow to significantly improve the quality of education provided by our schools, increase accountability of schools for their work, expand the autonomy of schools to develop their own curriculum to ensure the credibility of students and their parents to the national education system.